Efficiency and challenges of exosome and microRNA extraction from clinical biofluids in Indonesia: A commercial kit-based approach for qPCR applications - Aprilia Indra Kartika; Muchamad Dafip; Nastiti Wijayanti; Didik Setyo Heriyanto; Sofia Mubarika Haryana; Kartika Widayati Taroeno-Hariadi (Universitas Nahdlatul Ulama Surabaya, 2026)
Exosome miRNA has significant potential as biomarker for minimal or non-invasive diagnosis and monitoring of disease progression. However, extraction of miRNA exosomes from biofluids is challenging, and there is a lack of comparative evaluation of commercially available extraction kits for qPCR applications. Therefore, this study aims to obtain information about miRNA exosome extraction using commercial kits and analyze its expression with the qRT-PCR method. The exosome extraction was carried out using 3 types of commercial kits, while the RNA extraction was performed with a spin column. The purity and concentration of exosomes were measured using NTA, while total RNA was measured with nanodrops. Subsequently, miRNA expression was measured using qRT-PCR. The results showed that the concentration of exosomes obtained using kit 1 for plasma isolation was 3.5 x 1011 with particle sizes ranging from 30-240 nm. Kit 2 yielded a value of 2.9 x 1010 with particle sizes ranging from 30-150 nm, while kit 3 had no measurable value. The average concentration of RNA extracted using the RNA Basic kit from HansaBioMed was 42.53 ng/μL, while the exoRNeasy Midi kit from Qiagen yielded 45.28 ng/μL. Template RNA of 100 ng was converted into cDNA, while the cDNA was diluted at a ratio of 1:20 using RNase free water during the quantification process of miRNA exosome expression with the qRT-PCR method. Based on the results, exosome miRNA quantification process requires the use of the correct method at each stage to obtain the right expression for clinical studies.